Transformación de la hoja de coca (erythroxylum coca lamarck) en pan para consumo humano y su impacto socio económico - ambiental en las ciudades del alto huallaga - Obregón Lujerio, Abner Félix (2010)
We evaluated the problem of coca leaf and its transformation into bread consumption for human consumption, for proposals from the field to find food, probably disagreeing with those opinions regarding the eradication of coca substitution policies have not solved the reduction of supply or consumption; nor the decrease in cultivation, while social conflicts have increased among those who defend their only source of family support, the state and the gangs that promote corruption at all levels and create a macro distribution and consumption. Moreover, while there is an important industrial use of coca leaf, either in the field of medicine and in the manufacture of beverages and medicines, is not disseminated or objectively highlights these achievements, both ENACO by the Ministry of Agriculture that should promote their empowerment in the context of integrated watershed development coca. With this intention, we reached a diagnosis of coca production in the Upper Huallaga, with its positive and negative implications for alternative development in the cities of Alto Huallaga in 2000-2006, also discussed the medical benefits and food leaf and coca flour and a proposed alternative technology as a substitute for wheat flour at 5% level for a bread with 11% protein, 75% apparent digestibility and Protein Efficiency Ratio of 0,56, providing a nutritious, energy and nutraceuticals.